ANTHROPOMETRIC MEASUREMENT BASED ON STRUCTURE FROM MOTION IMAGING TECHNIQUE - S. Paśko; M. Sutkowski (Приборы и методы измерений)
The aim of this work was to estimate limitations related of the actual resolution of images taken into the object reconstruction procedure (using Structure from Motion method) applied for anthropometric measurements. This is necessary to define technical parameters of equipment used for this application. A series of 42 images of the sample static object were taken with use of high resolution camera. The object was in a stable position, properly illuminated with stable, diffused light sources. With use of VisualSFM software a virtual cloud of points representing real points of examined object was calculated. During tests a resolution of input images were changed then the calculation time and influence of the number of points in the cloud onto deviation of selected anthropometric parameters were analyzed. In conditions of the performed experiment decreasing of the resolution of input images to the level of 80 % of initial value (or lower) has significant influence onto results of the measurements of selected anthropometric parameters. Structure from Motion (SfM) technique can be adopted for anthropometric measurement systems when the input images are taken with high resolution imaging device (over a dozen of million pixels). Presented measurement method for anthropometry is characterized by ease of use, do not need any calibration before measurements or specialized equipment. Thank to this can be adopted in practice in any conditions and operated by unskilled operator.